Alterações cardiorrespiratórias na prole de ratas submetidas à dieta hiperlipídica - Barbosa, Rafaela Moreira (2018)
In recent decades obesity has become a worldwide epidemic. It has been shown that excessive adipose tissue favors the development of associated diseases such as hypertension, type II diabetes and ventilatory changes. In addition, maternal obesity may interfere in the programming and embryonic, fetal and neonatal development of the neuroendocrine system, increasing the risk of cardiorespiratory diseases from infancy to adulthood. Therefore, the objective of the present study was to evaluate the cardiovascular, ventilatory and metabolic responses in young (P28-35) and adult (P90) offspring of dams submitted to the high fat diet (HFD). Adult Holtzman dams (240 to 260 g) were submitted to standard diet (SD) or HFD for a period of 6 weeks before mating and during gestation and lactation periods. The offspring was standardized for 8 pups on the third day of life, and were weaned at P21 and only male offspring were used and were fed with SD from this period to the end of the experiments. In young offspring (P28-35 and P40) and adult offspring (P90), we analyzed: a) metabolic profile; b) food and water intake; c) ventilatory responses during the activation of chemoreflex under conditions of hypoxia and hypercapnia; and c) changes in baseline blood pressure and heart rate, as well as baroreflex sensitivity. The results showed that young offspring of dams fed HFD present several changes in the lipid and metabolic profiles, as well as a higher urinary sodium excretion, an increase in ventilatory response to hypoxia and a reduction in baroreflex function. In adult offspring, part of the cardiorespiratory function is partially recovered, although there are still some metabolic alterations, such as increase of the adipose tissue and the serum concentration of triglycerides. In addition, adult offspring of dams fed HFD present hyperphagia. The results show that the young offspring of dams fed HFD has autonomic, ventilatory and metabolic alterations. Partial recovery of cardiorespiratory function in adult offspring of dams fed HFD suggests that these possible intrauterine changes were partially corrected during postnatal development and were adequate in adult life.